Hubungan Jenis Kelamin terhadap Kejadian Stunting - Yuningsih Yuningsih; Dinar Perbawati (Universitas Islam Jember, 2022)
Stunting is a condition of failure to grow and develop in children which can result in morbidity, mortality, and decreased motor development. The incidence of stunting is often found in malnourished conditions. Jember is the district with the highest stunting incidence in East Java in 2020. Kaliwates Jember Health Center has a stunting incidence of around 460 at the age of 24-72 months. This research is observational with cross sectional approach. Taking non-random sampling of respondents using the N formula so that a sample of 82 was obtained and using statistical analysis using Chi Square. The results of data analysis from gender with stunting in toddlers obtained a value (p value = 0.04) = 0.05, which means that there is a relationship between sex and the incidence of stunting. The results of the study are expected that parents can maintain the health of their toddlers, try to serve foods that contain balanced nutrition according to the growth and development needs of toddlers and children as an effort to prevent and overcome stunting in toddlers.